1986
DOI: 10.1002/aja.1001760212
|View full text |Cite
|
Sign up to set email alerts
|

Different pharmacological anatomy in the paraventricular hypothalamic nucleus, supraoptic nucleus, and suprachiasmatic nucleus of rats: Quantitative autoradiography on angiotensin II receptor binding sites

Abstract: Angiotensin II (AII) and vasopressin (VP) play important roles in cardiovascular function. Using 125I-[Sar1,Ile8]-angiotensin II (125I-SI-AII), a potent AII antagonist, AII receptor binding sites were autoradiographically localized in three VP-producing areas of the hypothalamus and compared in hypertensive and normotensive rats. Within three major VP-producing areas, AII receptor binding was highest in the paraventricular hypothalamic nucleus and lowest in the supraoptic nucleus, suggesting that a differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…However, essentially equivalent OT secretory responses were obtained after administration of Ang II directly into the PVN/ACN, PVNcnt, SON and MBH. To our knowledge, this is the First report that OT release can be increased after direct Ang II stimulation of the magnocellular nuclei, but this finding is consistent with previous observations that Ang II receptors are present within the PVN and SON [41 ], that Ang 11 increases neuronal activity of a subpopu lation of putative SON OT neurons in vitro [39,42], and that Ang Il-immunopositive fibers, derived from subfor nical organ, innervate the SON [43]. The response to Ang 11 in the MBH may be indirect as this region is known to project to the PVN [ 18].…”
Section: Discussionsupporting
confidence: 82%
“…However, essentially equivalent OT secretory responses were obtained after administration of Ang II directly into the PVN/ACN, PVNcnt, SON and MBH. To our knowledge, this is the First report that OT release can be increased after direct Ang II stimulation of the magnocellular nuclei, but this finding is consistent with previous observations that Ang II receptors are present within the PVN and SON [41 ], that Ang 11 increases neuronal activity of a subpopu lation of putative SON OT neurons in vitro [39,42], and that Ang Il-immunopositive fibers, derived from subfor nical organ, innervate the SON [43]. The response to Ang 11 in the MBH may be indirect as this region is known to project to the PVN [ 18].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the Ang II-induced effects are inhibited by a lower dose of [Sar1, Ile$]Ang II in the SON than in the PVN. Also, this is consistent with evidence from auto radiographic binding studies that the Ang II receptor concentration is higher in the PVN than in the SON (8,10). It is suggested that Ang II receptors exist on cell bodies of vasopressin-containing neurons in the nuclei and direct ly promotes vasopressin release (11)(12)(13)(14).…”
Section: Effects Of Antagonists On Ang Ii-induced Antidiuresessupporting
confidence: 77%
“…Vasopres sin-containing neurons are activated by Ang II (12 14). Also, Ang II receptors, neurons and terminals of Ang II containing neurons are involved in the SON, as well as in the PVN (6,8,15).…”
mentioning
confidence: 99%
“…All of the components of the renin-an giotensin system, including angiotensin II itself, are found in the brain [10, II], Specific angiotensin II receptors have been demonstrated throughout the central nervous system [10,12,24,29,31]. It has been shown repeatedly that the injection of angiotensin II into the cerebral ventricular system stimulates vasopressin release in many species [16,28,37,48].…”
Section: Introductionmentioning
confidence: 99%